Blood antioxidant parameters in subjects from Azorean populations with different sociocultural profile - Pavão, Maria Leonor (2014)
Abstract de Comunicação em Painel (PS4-02730) apresentada em "27th Meeting of the Federation of European Biochemical Societies (FEBS)", 30 Jun-6 Jul, 2001, Lisboa, Portugal.